Mengenali Potensi Dan Pengalaman Karir Individu Para Disabilitas - Muhammad Gilang Putra Tryana; Dini Dwi Rai Anggraeni; Virgifan Afandi Yanto; Jihan Fikriyyah; Dian Aulia Mareti; Siti Hamidah (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
In the midst of job competition between countries in Asia, people with disabilities must also fight for their place in the job market. People with disabilities, who may face physical, mental, intellectual, motor and sensory barriers, face the additional challenge of finding employment commensurate with their abilities and barriers. Although the Indonesian government has made efforts to provide equal rights to people with disabilities through laws and policies, many challenges remain. Many people with disabilities are forced to work in the informal sector with low wages, and low participation. Therefore, research on the career prospects and experiences of individuals with disabilities is important in identifying the obstacles faced and exploring solutions that can improve disability inclusion in the world of work. Literature studies can provide valuable insights into the potential and problems experienced by people with disabilities in finding and maintaining employment, and provide a basis for the development of more inclusive policies and more effective support. By encouraging better accessibility and providing appropriate support services, communities and governments can help people with disabilities develop their potential and achieve success in their careers, while ensuring that work environments become more inclusive for all individuals, regardless of background or physical condition.